¿Es la privatización la solución a los problemas de ineficiencia de las empresas públicas?: Revisión de la literatura (2012)
This paper presents the state of the art of the effect of the privatization on the results of the public enterprises from 1990 to the present. A thorough review was carried out, nationally and internationally, on the works analyzing the effect of privatization on the performance of firms subject to ownership changes. Thus, we found that privatization led to improvements in performance and efficiency of some of the companies. Nevertheless, the relationship between ownership and efficiency cannot be taken as a rule, as evidence shows that public companies are not always more inefficient. In Colombia, there are still many unanswered questions due to the lack of studies analyzing the subject.